2019
DOI: 10.1007/s13204-019-00993-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of seawater on the hydration, microstructure and strength development of Portland cement pastes incorporating colloidal silica

Abstract: This contribution investigates the effects of seawater and colloidal silica (NS) in the amounts of 1, 3 and 5 wt%, respectively, on the hydration, strength development and microstructural properties of Portland cement pastes. The data reveal that seawater has an accelerating effect on cement hydration and thus a significant contribution to early strength development was observed. The beneficial effect of seawater was reflected in an improvement in compressive strength for up to 14 days of hydration, while in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 47 publications
(62 reference statements)
3
55
0
Order By: Relevance
“…These observations are in line with the work of Demir et al (2010), where only marginal effects of SF incorporation in concrete mixes with seawater were observed. In contrast, Sikora et al (2019b) have recently reported the beneficial effect of combining nanosilica and seawater on the acceleration of hydration processes and the early strength development of OPC systems.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…These observations are in line with the work of Demir et al (2010), where only marginal effects of SF incorporation in concrete mixes with seawater were observed. In contrast, Sikora et al (2019b) have recently reported the beneficial effect of combining nanosilica and seawater on the acceleration of hydration processes and the early strength development of OPC systems.…”
Section: Introductionmentioning
confidence: 93%
“…The solid mass of the NS suspension was 50 wt% and as such, the liquid phase of the suspension was considered as a part the of mixing water in the production of the cement pastes and mortars. The same NS structures have been used in previous studies and have been comprehensively characterized in the work of Sikora et al (2019b). High-resolution transmission electron microscope (TEM) micrographs ( Fig.…”
Section: Nanosilica Properties and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations